Ella at Zardi's [compact disc] - Fitzgerald, Ella (Verve Label Group, 2017)
"Rescued from the vaults: Ella At Zardi's is the Verve Records' first live recording, and is being heard for the first time anywhere. The two sets from the evening, in front of a lively crowd, was captured February 2, 1956, a few days before Ella began recording Verves first album, Ella Fitzgerald Sings The Cole Porter Song Book." -- Amazon.